Why small-scale irrigation makes for good nutrition policy - Lefore, Nicole; Ringler, Claudia (AgriLinks, 2023)
The Feed the Future Innovation Lab for Irrigation and Mechanization Systems (ILIMS), led by the University of Nebraska’s Daugherty Water for Food Global Institute (DWFI) (Nebraska-ILIMS), was fittingly launched at this year’s World Food Day with the theme “Water is Life, Water is Food. Leave No One Behind.” The research program’s five areas of inquiry will develop socio-technical bundles that support uptake of mechanization and irrigation, strengthen institutions for natural resource governance and climate resilience, enable scaling of suitable technologies and support development of human resources. The fifth area of inquiry makes a leap from technology to nutrition and health, with the specific aim to “formulate strategies for nutrition-sensitive mechanization and irrigation that safeguard and enhance health and inclusivity.”